Upaya Peningkatan Volume Penjualan UKM Kampung Lumpia Ngaglik Gang Kuburan Surabaya di Masa Pandemi COVID-19 - Arief, Zainal; Herlina, Herlina (Jurnal Pengabdian Masyarakat dan aplikasi Teknologi, 2022)
Kampung lumpia, located on Jalan Ngaglik, Surabaya graveyard, is a home industry (IRT) managed by Mr. Kasmono as the owner. This business was initiated in 2009. The number of employees employed on the production floor is 4 people, and 3 employees to sell spring rolls in groups. The problem for SMEs is that minimal capital makes the owner not replace the pans and stoves for making spring roll skins and frying spring rolls. The frying pan and stove have been used for 10 years since this business was founded so that it is black and charred and the addition of 1 new rombong unit to increase market share in other sales locations. In terms of marketing, it is still done offline using a group, the owner wants to try marketing online, for example advertising to receive orders on online social media. In terms of selling price, the spring rolls and risoles that are produced are sold at a price of Rp. 1,500.00 per seed. The owner does not know the bookkeeping and calculation of the cost of production for the spring rolls and risoles that he sells, so training on the calculation of the cost of production is necessary.